(untitled) (Research, Society and Development, 2025)
While conventional Primary Health Care faces major challenges in promoting Brazilian health, Primary Indigenous Health Care, little addressed by science, experiences additional problems to conventional challenges. The provision and retention of health professionals in indigenous territories, the adoption of work processes capable of addressing the needs and specificities of Indigenous users, and the harmonious coexistence between academic medicine and indigenous medicine make up important challenges faced by the health systems of Brazilian Indigenous people. This study aimed to explore the challenges faced by Brazilian Indigenous Primary Health Care considering three categories of analysis: provision and retention of professionals; work processes; and interculturality with Indigenous medicines. Documentary research was carried out using direct and indirect sources of a qualitative nature and was reflective. The central discussions presented bring intercultural training as an important weakness in all categories of analysis, at the same time it presents itself as a powerful tool to advance the challenges proposed by the work. Thus, the conclusion presented in this study points to the need for investments in training processes, work management, and care processes, considering interculturality as a transversal theme in the actions to be developed.